Islamic perspective to healthcare architecture - Mohd Nawawi, Norwina (2002)
Introduction The very word “Islam” meaning “Peace” in its righteous usage has to most populace a different connotation altogether. Islam, a religion of peace and Muslims as those who profess the Islamic religion as the way of life, is being looked upon differently by the non-Muslim depending on situation, how the religion is being presented, where, by whom and its application in the ICT age. Like all other great religion, Islam condones good universal values that transcend time, place, race, colour, creed, social status, gender and its application to Muslims and the Non-Muslims as creatures of God. In healthcare, Islam and Muslims had played major roles in the history of medicine. However, little has been said or written about the healthcare facilities it harbours.